2013
DOI: 10.1002/jgrc.20316
|View full text |Cite
|
Sign up to set email alerts
|

Coupled nitrate nitrogen and oxygen isotopes and organic matter remineralization in the Southern and Pacific Oceans

Abstract: [1] The difference between nitrate 15 N and 18 O, or D(15-18), is sensitive to organic matter remineralization and tracks the modification of nitrate as it passes from the deep Pacific Ocean, through the Southern Ocean surface, and into the intermediate-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
225
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(283 citation statements)
references
References 64 publications
17
225
1
Order By: Relevance
“…2a, b). Such values are similar to those observed widely for the deep ocean (see Di-Fiore et al, 2009;Sigman et al, 2000Sigman et al, , 2009bRafter et al, 2013). Although δ 18 O NO 3 values are more scattered, it can be clearly seen that they follow a pattern similar to δ 15 N NO 3 , with values up to 6 ‰ in surface waters, which decrease to < 2 ‰ in the 500 to 1000 m depth interval but tend to increase again in deep and bottom waters and stay close to 2 ‰ (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…2a, b). Such values are similar to those observed widely for the deep ocean (see Di-Fiore et al, 2009;Sigman et al, 2000Sigman et al, , 2009bRafter et al, 2013). Although δ 18 O NO 3 values are more scattered, it can be clearly seen that they follow a pattern similar to δ 15 N NO 3 , with values up to 6 ‰ in surface waters, which decrease to < 2 ‰ in the 500 to 1000 m depth interval but tend to increase again in deep and bottom waters and stay close to 2 ‰ (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In the present study the effect of NO − 2 was neglected since overall nitrite concentrations were small, representing on average < 0.5 % of the nitrate + nitrite pool (see also DiFiore et al, 2009). However, it has been reported that slightly higher nitrite levels reaching 0.8 % of the nitrite + nitrate pool such as observed here for the surface waters can result in a lowering of the δ 15 N and δ 18 O values by 0.4 and 0.2 ‰ on average (Rafter et al, 2013; their Supplement). We have not corrected our surface water nitrate isotopic values for a possible nitrite effect, as is the case also in work presented by others (see e.g., DiFiore et al, 2009;Rafter et al, 2013), but have considered the impact of this when calculating nitrification (see Sect.…”
Section: Sampling and Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…[Granger et al, 2004[Granger et al, , 2008[Granger et al, , 2010Karsh et al, 2012Karsh et al, , 2014. [Rafter et al, 2013;Smart et al, 2015]. In the T min , NO 3 À + NO 2 À samples fall slightly above the 1:1 line in δ 18 O versus δ 15 N space, reflecting the decrease in NO 3 À δ 15 N relative to ln(NO 3 À ) within the T min layer (i.e., the kink).…”
Section: Non-rayleigh Dynamics and Estimation Of Isotope Effectsmentioning
confidence: 95%
“…were less stressed for iron (Chappell et al, 2012 Hoering and Ford, 1960;Minagawa and Wada, 1986). In contrast, in the Pacific, NO 3 -mixed up from the subsurface is impacted by water column denitrification and can have a NO 3 -δ 15 N >20‰ (e.g., (Brandes et al, 1998;Casciotti et al, 2013;Rafter and Sigman, 2016)), although as upper thermocline waters move westward in the Pacific, the very high NO 3 -δ 15 N signal is diluted and typical values are between 5 and 10‰ (Rafter et al, 2013). The relative importance of each source for 25 supporting export production can be determined using the two end-member mixing model described in Eqn.…”
mentioning
confidence: 99%